Unchanged serum levels of advanced glycation endproducts in patients with liver disease - Butscheid, Moritz; Schäfer, Christian; Brenner, Stefanie; Alscher, Dominik; Mürdter, Thomas; Niwa, Toshimitsu; Frischmann, Matthias; Pischetsrieder, Monika; Klotz, Ulrich (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)
Advanced glycation end products (AGEs), e.g., carboxymethyllysine (CML) or imidazolone are involved in several age-related disorders. Concerning their accumulation, the importance of hepatic and renal function is controversially discussed. To test whether impairment of hepatic or renal function will affect their accumulation, both AGEs have been measured in various populations, such as 52 patients with liver disease [viral hepatitis C without (n = 19) and with (n = 10) fatty liver; nonalcoholic fatty liver (n = 13), nonalcoholic steatohepatitis (n = 10)]. Serum concentrations of both AGEs have been compared to those in 20 healthy controls and 24 patients with moderate renal impairment (creatinine clearance 23-55 ml/min). Concerning CML (95% C.I. 803-1200 ng/ml), no differences between the various groups could be observed. Likewise, serum levels of imidazolone (95% C.I. 1.3-5.6 units) were similar in all populations. In conclusion, moderate impairment in hepatic or in renal function did not affect serum levels of CML and imidazolone. Apparently, any increase observed in severe cirrhosis or renal failure seems to be rather a consequence than a cause of both disorders. © 2007 Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2007.nat.dchph.llmch.unchan
Keywords: Accumulation; Carboxymethyllysine; Elimination; Imidazalone; Liver disease; Renal impairment